2010
DOI: 10.1002/cncr.25473
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker‐based phase I dose‐escalation, pharmacokinetic, and pharmacodynamic study of oral apricoxib in combination with erlotinib in advanced nonsmall cell lung cancer

Abstract: BACKGROUND: Apricoxib, a novel once-daily selective cyclooxygenase-2 inhibitor, was investigated in combination with erlotinib for recurrent stage IIIB/IV nonsmall cell lung cancer to determine the maximum tolerated dose, doselimiting toxicity, and recommended phase II dose (RP2D) based on changes in urinary prostaglandin E 2 metabolite (PGE-M). METHODS: Patients received escalating doses of apricoxib (100, 200, and 400 mg/day) in combination with erlotinib 150 mg/day until disease progression or unacceptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…PGE 2 can transactivate EGFR, which can subsequently increase expression of COX-2. In addition, PGE 2 , via promotion of epithelial-to-mesenchymal transition (EMT), can increase resistance to EGFR inhibitors (22). Furthermore, short circuiting both pathways simultaneously can have synergistic effects in preclinical cancer models (2325).…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 can transactivate EGFR, which can subsequently increase expression of COX-2. In addition, PGE 2 , via promotion of epithelial-to-mesenchymal transition (EMT), can increase resistance to EGFR inhibitors (22). Furthermore, short circuiting both pathways simultaneously can have synergistic effects in preclinical cancer models (2325).…”
Section: Introductionmentioning
confidence: 99%
“…They selected NSCLC patients based on a 50% decrease from baseline levels of a urinary metabolite of PGE2 (PGEM) in response to apricoxib, but the primary endpoint of the trial was not met, possibly due to the low cutpoint for the decline in PGEM [65]. Reckamp et al evaluated COX-2 expression in a phase II trial [66] by measuring levels of baseline PGEM based on results of their phase I trial in NSCLC [67,68]. They reported that COX-2 pathway represents a novel mechanism of resistance to EGFR TKI therapy in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease, associations between disease states and sphingolipid contents or abnormality of cell membrane component both in brain and in cholesterol metabolism have been reported [6][7][8][9][10][11]. For cancer, prostaglandins and leukotrienes regulated tumor proliferation have been suggested [12,13] and as a result inhibitors for prostaglandin synthesis have been proposed as anticancer agents [14,15]. Similarly, breast cancer and prostate cancer could also be explained in part by the imbalance of steroid hormones [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%